2003
DOI: 10.1002/ijc.10970
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants of incidence of primary fallopian tube carcinoma, Finland 1953–97

Abstract: Primary fallopian tube carcinoma is very rare. In Western countries, it accounts for about 1% of all female genital malignant tumors. Its etiology remains poorly known, but high parity is considered to be protective. We studied determinants of incidence of primary fallopian tube carcinoma in Finland. Incidence rates for primary fallopian tube carcinoma, according to the population based Finnish Cancer Registry, from 1953-97 were assessed by age, year of diagnosis, and type of residential area. Standardized inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
79
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 21 publications
2
79
1
3
Order By: Relevance
“…The U.S. incidence rate for PFTC (0.41 per 100,000) was similar to those reported in Denmark and Finland of 0.3 and 0.5 per 100,000, respectively [22,23]. White women in the United States had significantly higher rates of PFTC than other women, a finding consistent with ovarian cancer.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The U.S. incidence rate for PFTC (0.41 per 100,000) was similar to those reported in Denmark and Finland of 0.3 and 0.5 per 100,000, respectively [22,23]. White women in the United States had significantly higher rates of PFTC than other women, a finding consistent with ovarian cancer.…”
Section: Discussionsupporting
confidence: 73%
“…Incidence rates peaked at an older age (70-79) in our study, but most previous studies reported peak incidence occurring in the early 60s [15,22,27]. Population-based registries contributing data to these studies included cases diagnosed 10-50 years ago [15,22]; however, while our study included diagnoses from the last 4-9 years.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations